2018
DOI: 10.1016/j.jtho.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Pulmonary Ground-Glass Opacities with Folate Receptor–Targeted Intraoperative Molecular Imaging

Abstract: This approach provides a safe alternative for intraoperative localization of small, peripherally located pulmonary lesions. In contrast to alternative localization techniques, use of OTL38 also allows confirmation of adequate margins. Future studies will compare this approach to alternative localization techniques in a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…In this trial, there were no drug-related adverse events observed perioperatively or within 30 days postoperatively (20). Sixteen of 21 tumors with GGO displayed lesion-specific fluorescence during NIR imaging, and the depth from the pleural surface was the sole determinant for the successful detection of lesions by intraoperative molecular imaging.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In this trial, there were no drug-related adverse events observed perioperatively or within 30 days postoperatively (20). Sixteen of 21 tumors with GGO displayed lesion-specific fluorescence during NIR imaging, and the depth from the pleural surface was the sole determinant for the successful detection of lesions by intraoperative molecular imaging.…”
mentioning
confidence: 73%
“…Predina and his colleagues have very recently published the data of intraoperative molecular imaging using OTL0038 for pulmonary small nodules with GGO in the Journal of Thoracic Oncology (20). This study recruited 20 patients with 21 pulmonary tumors, comprising nine pure GGOs and 12 GGOs with a solid component, which were suspicious for lung neoplasms.…”
mentioning
confidence: 99%
“…[19][20][21] First, the initial experience showed that FR-targeted IMI was successful not only for adenocarcinomas but also for ground glass opacities, a potential precursor for malignant lung adenocarcinoma, and a rapidly growing problem in the United States and Asia. 22 The second finding from the pilot studies was that IMI combined with PET was superior in detecting and locating tumors for removal; in fact, IMI was better than PET for locating nodules <1 cm. 23 Finally, despite theoretical specificity for lung adenocarcinomas, lung squamous cell carcinomas were also sensitive to OTL38 because of off-target effects on FR-beta positive tumor-associated macrophages.…”
Section: Folate Receptor Alpha For Lung Adenocarcinomamentioning
confidence: 96%
“… 22 This molecular imaging technology used in cancer surgery mainly focuses on breast and hollow viscus, such as the respiratory and gastrointestinal tracts. 23 , 24 , 25 Optical molecular imaging can specifically show the pathological process related to tumorigenesis and provide real-time macroscopic imaging of tumor tissue in vivo . Therefore, it could be used to improve the quality of NMIBC management, such as detection of small or occult tumor lesions and evaluation of the status of surgical margin and depth of tumor invasion during tumor resection.…”
Section: Main Textmentioning
confidence: 99%